2D Silver Nanosheets: Ultrafast Growth of Large 2D Silver Nanosheets by Highly Ordered Biological Template at Air/Gel Interface (Adv. Mater. Interfaces 10/2018). Issue 10 (22nd May 2018) - Jang, Hyung‐Seok; Seong, Baekhoon; Zang, Xining; Lee, Hyungdong; Bae, Jin Woo; Cho, Dae‐Hyun; Kao, Emmeline; Yang, Chen; Kang, Giho; Liu, Yumeng; Park, Hyun Sung; Byun, Doyoung; et al.
Abstract : Biological template can be utilized to align the molecular orientation for large grain size in the synthesis of the high‐quality two‐dimensional silver nanostructure. The multi‐layering phenomenon of hydrogel forms biological template at the air/gel interface and supports the silver salts to grow laterally and largely in a two‐dimensional manner between the scaffold layers with a nominal thickness of 4.4 ± 0.3 nm. This is reported by Doyoung Byun, Liwei Lin co‐workers in article number1701491 .